COMPARATIVE STUDY OF THE INTERNATIONAL FINANCIAL REPORTING STANDARD IMPLEMENTATION IN GHANA AND NIGERIA - Evans O.N.D. Ocansey; John A. Enahoro (European Scientific Journal, ESJ, 2014)
The globalization of the world’s economy and markets led companies and nations to become world global players. In addition, more investments take place on a global level. Before the adoption of International Financial Reporting Standards (IFRS), different countries developed their own national accounting standards or adopted that of other countries. However, movement of business toward a global economy brought challenges in comparability, objectivity, reliability, understandability among others. These issues have accelerated the need to move toward global accounting standards. Thus these challengesspelt the need for a single set of high quality and globally accepted accounting standards. Ghana and Nigeria are major trade partners and due to different timing of the adoption of IFRS, this research was conducted tocompare the IFRS adoption and implementation of these countries through a literature review. It was found that Ghana and Nigeriacommenced the adoption process in 2005 and 2010 respectively. It was revealed that, the national standards of Ghana and Nigeria were closely related and had both suffered lack of certain standards and disclosurerequirements. Besides, it was revealed that the IFRS’adoption and implementation demands a new set of skills and expertise, transitional challenges,dealing with inconsistencies in applicable laws, emerging technical areas and terminologies; also frequent reviews of standards, higher demand for auditors among others despites the benefits that came with it.This study recommends that, both Ghana and Nigeria should work on skills and expertise gap through training and development andto ensure that these standards are included in the academic and professional curricula. Moreover, regulatory bodies should monitor and enforce these standards but where local content is needed, convergence should be the solution.